Pengembangan Aplikasi Manajemen Tugas berbasis Android (Studi pada CV. Cheleron Production) - Iqra Ilhamsyah; Agi Putra Kharisma; Novanto Yudistira (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Management is an important sector in performing a task. One of the agencies that use management to perform a task is CV. Cheleron Productions. Currently CV. Cheleron Production has several problems in task management which lie in the absence of a place for integration of existing job data, no monitoring of work progress, no task scheduling, and no special format for work. Therefore, it takes a task management application that is expected to help CV. Cheleron Production solves these problems. This application can be developed using the Software Development Life Cycle (SDLC) Waterfall Model using an Object-oriented (OO) approach to the analysis and design process. Development is carried out with an Android-based implementation using the Java programming language. Testing is done by unit testing, integration testing, and validation testing. Unit testing is carried out using one of the White-box testing methods, namely Basis Path Testing, integration testing is carried out using Top-down Integration Testing, and validation testing is carried out using the Black-box method.